1991
DOI: 10.1101/gad.5.4.629
|View full text |Cite
|
Sign up to set email alerts
|

A cold-sensitive mRNA splicing mutant is a member of the RNA helicase gene family.

Abstract: We have isolated a cold-sensitive mutant of Saccharomyces cerevisiae in which the first step of mRNA splicing is inhibited. The growth and splicing defects are recessive and cosegregate, thus defining a single essential gene (PRP28). The wild-type PRP28 gene was cloned, and sequence analysis reveals extensive homology to a family of proteins that are thought to function as ATP-dependent RNA helicases. The cold sensitivity is caused by a glycine-to-glutamic acid change in a conserved sequence motif. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
2

Year Published

1992
1992
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 75 publications
3
99
0
2
Order By: Relevance
“…Since PRP2 activity is an essential requirement for the first transesterification reaction (27) PRP2A spliceosomes could not process pre-mRNA into spliced mRNA (Fig. 3A, lanes 3-5), and they formed splicing complex I but no splicing complex 11 (28,29 and data not shown). Complementation with a heat-inactivated temperature-sensitive prp8 extract restored splicing activity (Fig.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since PRP2 activity is an essential requirement for the first transesterification reaction (27) PRP2A spliceosomes could not process pre-mRNA into spliced mRNA (Fig. 3A, lanes 3-5), and they formed splicing complex I but no splicing complex 11 (28,29 and data not shown). Complementation with a heat-inactivated temperature-sensitive prp8 extract restored splicing activity (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…A prp8 allele has been isolated as a genetic suppressor ofthe DEAD-box protein splicing factor PRP28, a putative RNA helicase. From this a model was proposed in which PRP28 protein destabilizes the U4/U6 snRNA interaction prior to step 1 of splicing, counterbalanced by a stabilizing effect of PRP8 protein (11). A mutation affecting another DEAD-box protein, DED1, has been isolated as a cold-sensitive suppressor of a temperature-sensitive prp8 allele (12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-discussed contacts with the pre-mRNA, Prp8 is expected to interact with a number of spliceosomal components+ An allele of PRP8 ( prp8-201) was found to suppress a cold-sensitive allele of U4 snRNA+ The mutation in prp8-201 maps close to the region involved in polypyrimidine tract recognition (Kuhn et al+, 1999;Umen & Guthrie, 1996)+ Prp40, a component of yeast U1 snRNP, physically interacts with the proline-rich domain at the N-terminus of yPrp8 (Abovich & Rosbash, 1997)+ Finally, Prp8 was shown to genetically interact with two putative helicases: DED1 (Jamieson et al+, 1991) and Prp28 (Strauss & Guthrie, 1991)+ Interestingly, the human homolog of Prp28 (U5-100kD) is also an integral component of the U5 snRNP (Teigelkamp et al+, 1997), suggesting that Prp8 may directly interact with Prp28 and possibly other U5 snRNP components, including U5 snRNA+ While the crosslinking studies have confirmed a close contact between Prp8 and pre-mRNA, Prp8 also has been shown to interact with a series of other spliceosomal components throughout the reaction+ Thus, it is likely that Prp8 plays a central role in splicing, coordinating a series of events through interactions with several spliceosomal components, and perhaps participating in formation of the active site of the splice-osome+ This could be achieved either by providing a binding site for the splice sites, or possibly also by contributing to the chemical reaction in a more direct way+ At present, the mechanistic details concerning the pre-mRNA splicing catalysis are not known+ The catalytic center is likely to involve a combination of specific RNA:RNA interactions and other contacts that rely on amino acid residues+ Because of the discussed close contacts between Prp8, pre-mRNA, and other spliceosomal components, as well as the established RNA: RNA interactions involving U2 and U6 snRNAs, it seems likely that Prp8, along with U2 and U6 snRNAs, participates in formation of the catalytic center+…”
Section: Prp8 Interacts With Multiple Spliceosomal Componentsmentioning
confidence: 99%
“…However, genetic approaches have led to the isolation of many splicing deficient mutants, called prp mutants (20,21). Some PRP genes encode snRNP components, such as PRP4, PRP8 and PRP24 (14,19,(22)(23)(24) and others, such as PRP2, PRP5, PRP9, PRP11, PRP16, PRP22 and PRP28, are implicated in spliceosome assembly or disassembly (25)(26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%